Historical-Research Overview of Socio-Economic and Politico-Legal Basis for the International Relations of Kazakhstan on the Post-Soviet Space (1991 – 1995) - KARASAYEV, Gani M.; DUISEN, Seytkali Zh.; NAIMANBAYEV, Bekmurat R.; ZHUMAGULOV, Bolat S.; AMINOV, Talgatbek M. (Journal of Advanced Research in Law and Economics; Vol 10 No 7 (2019): JARLE Volume X Issue 7(45) Winter 2019, 2019)
The research is devoted to the history of the foundation and formation of the CIS states and the place of the First President of Kazakhstan N.A. Nazarbayev in its substantiation. The authors have included the materials of archives of the President of Kazakhstan (AP RK) and archives of the foreign policy of the Russian Federation (AFP RF) in the scientific circulation to open the relationships between states. Moreover, they quoted to the works of foreign and Kazakhstani figures. The formation and establishment of the CIS states on the post-soviet space are important issues. Therefore, the research article considers political, economic and diplomatic relations in the modern world as a subject of historical relations and historical events. Therefore, this article is a study of the ways of formation and ways of historical development of CIS countries.